Metal regulated organic–inorganic hybrid ferroelastic materials: [(CH3)3CN(CH3)2CH2F]2[MBr4] (M = Cd and Zn). Issue 8 (24th February 2022) - Meng, Xin; Liu, Zhi-Bo; Xu, Ke; He, Lei; Wang, Yu-Zhen; Shi, Ping-Ping; Ye, Qiong
Abstract : Two organic–inorganic hybrid compounds [(CH3 )3 CN(CH3 )2 CH2 F]2 [MBr4 ] (M = Cd and Zn) undergo ferroelastic phase transitions. The substitution of metal center Cd with Zn of inorganic anions regulate the ferroelastic phase transitions. Abstract : Two organic–inorganic hybrid compounds [(CH3 )3 CN(CH3 )2 CH2 F]2 [MBr4 ] (M = Cd for 1 and Zn for 2 ) undergo ferroelastic phase transitions with the Aizu notation of mmmF 2/ m, accompanied by dielectric switches. The replacement of the metal center Cd with Zn increases the ferroelastic phase transition temperature ( T c = 246 K, 262 K for 1 and 2, respectively) and the spontaneous strain value from 0.131 in compound 1 to 0.422 in 2 . This work offers an effective strategy to regulate the ferroelastic phase transition by introducing different metal centers into organic–inorganic hybrid materials.